Aden W. Hayes, Roberto Arlt: la estrategia de su ficción. Tamesis Books, London, 1981; 82 pp. (Monografías, 83). - Olea Franco, Rafael (El Colegio de México, 1983)
Se reseñó el libro: Roberto Arlt: la estrategia de su ficción.